(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The family Asteraceae include large number of Centaurea species which have been applied in folk medicine. One of the family Asteraceae members is the Centaurea damascena which authentically been tested for its antibacterial activity. The aim of the study was to discuss antibacterial activities of essential oil composition and methanolic extract of the same plant aerial part leaves. Thirty-seven components were characterized with 86% of oxygenated terpenes. The composition was dominated by 11.45% Fokienol, 8.8% thymol, 8.21% Alpha Terpineol, 7.24% Chrysanthemumic acid, 7.13% Terpinen-4-ol and 6.59% Borneol with a high degree of polymorphism in the occurrence of these compounds as compared with the different species of centaurea.. Free radical scavenging capacity of the C. damascna methanol extract was calculated by DPPH and FRAP test. DPPH radicals were scavenged with an IC50 value of 17.08 µg /ml. Antioxidant capacities obtained by the FRAP was 51.9 and expressed in mg Trolox g-1 dry weight. The total phenolic compounds of the methanol extracts of aerial parts, as estimated by Folin–Ciocalteu reagent method, was about 460 mg GAE/ g. The phenolic contents in the extracts highly correlate with their antioxidant activity, (R2 = 0.976) confirming that the antioxidant activity of this plant extracts is considerably phenolic contents-dependent.